2022
DOI: 10.1155/2022/1353778
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Mitigates Microglial Activation Associated with Postoperative Cognitive Dysfunction by Modulating the MicroRNA-103a-3p/VAMP1 Axis

Abstract: Surgery-induced microglial activation is critical in mediating postoperative cognitive dysfunction (POCD) in elderly patients, where the important protective effect of dexmedetomidine has been indicated. However, the mechanisms of action of dexmedetomidine during the neuroinflammatory response that underlies POCD remain largely unknown. We found that lipopolysaccharide (LPS) induced substantial inflammatory responses in primary and BV2 microglial cells. The screening of differentially expressed miRNAs revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Perioperative administration of Dex also significantly improves early postoperative cognitive function in children undergoing tonsillectomy (Peng et al, 2021). Studies have found that Dex injection during laparoscopic cholecystectomy reduces serum proinflammatory cytokines and the occurrence of POCD (Wu et al, 2022; Yu et al, 2022). Dex was shown to reduce the severity of neuroinflammation and neuronal apoptosis in animal models of systemic inflammatory response syndrome (SIRS) and surgical injury (Du et al, 2021; Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative administration of Dex also significantly improves early postoperative cognitive function in children undergoing tonsillectomy (Peng et al, 2021). Studies have found that Dex injection during laparoscopic cholecystectomy reduces serum proinflammatory cytokines and the occurrence of POCD (Wu et al, 2022; Yu et al, 2022). Dex was shown to reduce the severity of neuroinflammation and neuronal apoptosis in animal models of systemic inflammatory response syndrome (SIRS) and surgical injury (Du et al, 2021; Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For the open field test, the mice were housed in an open square plywood box and painted with flat black enamel paint (overall measurements of 72 cm (length), 30 cm (height), and 72 cm (breadth)) ( 21 ). Artificial light and darkness conditions were used to simulate the day and night environment.…”
Section: Methodsmentioning
confidence: 99%